The equivocal image of young social enterprises—How self- versus other-oriented values influence external perceptions - Yasmine Yahyaoui; Eva A. Jakob; Holger Steinmetz; Marius C. Wehner; Rodrigo Isidor; Rüdiger Kabst (Nonprofit Management and Leadership, 2023)
Social enterprises follow the dual mission of achieving social aims as well as attaining financial sustainability and therefore elude easy categorization into either a non-profit or for-profit organization. Consequently, social enterprises might struggle with their image since external stakeholders (e.g., job applicants and customers) could hold back their support when the enterprise's dual aims seem unusual to them. Despite the importance of the image to gain stakeholder support, factors that determine how individuals perceive social enterprises are underexplored, especially in their early life stages before they have developed reputational capital and brand recognition. Following human value theory, we propose that stakeholders' self-transcendence (“other-oriented”) versus self-enhancement (“self-centered”) values explain how they evaluate social versus commercial enterprises. In a vignette study with 945 individuals, we reveal that social enterprises are more likely to attract self-transcendent individuals whereas individuals with stronger self-enhancement values are less likely to feel attracted to social enterprises. Moreover, our findings show that individuals' values were more strongly related to the image of social enterprises than to the image of commercial enterprises. Thus, external individuals' values lead to stronger and more contrasting reactions regarding social compared to commercial enterprises. The findings indicate that the image of social enterprises is more equivocal and distinct compared to commercial enterprises and therefore might require a different theoretical understanding and careful management as it depends on stakeholders' deep-seated values.
Keywords: 650; enterprise image; external perceptions; human value theory; self-enhancement; self-transcendence; social enterprises